2008
DOI: 10.1086/592402
|View full text |Cite
|
Sign up to set email alerts
|

Zero Sum, the Niche, and Metacommunities: Long‐Term Dynamics of Community Assembly

Abstract: Recent models of community assembly, structure, and dynamics have incorporated, to varying degrees, three mechanistic processes: resource limitation and interspecific competition, niche requirements of species, and exchanges between a local community and a regional species pool. Synthesizing 30 years of data from an intensively studied desert rodent community, we show that all of these processes, separately and in combination, have influenced the structural organization of this community and affected its dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 123 publications
4
104
1
Order By: Relevance
“…The literature on the temporal dynamics of energy flow and functional compensation is limited to modern-day ecological studies spanning at most several decades (3,4,6,20), with only one historical snapshot comparison extending back to a century (5). This is despite the urgent need to understand natural variability and establish baselines against which to evaluate ecosystem function in today's rapidly changing world (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on the temporal dynamics of energy flow and functional compensation is limited to modern-day ecological studies spanning at most several decades (3,4,6,20), with only one historical snapshot comparison extending back to a century (5). This is despite the urgent need to understand natural variability and establish baselines against which to evaluate ecosystem function in today's rapidly changing world (21).…”
Section: Discussionmentioning
confidence: 99%
“…This limits direct comparison with modern ecological studies, but nonetheless provides insight into the compensatory dynamics of community functional structure and the contribution of individual and species body size distributions to sample-standardized energy flow. The consideration of metabolic theory, a century-scale resurvey of small mammals in a Great Basin mountain range (5), and decadal-scale studies of granivorous rodents at the Portal long-term ecological research site in Arizona (20) offers hypotheses for the mechanisms controlling the functional compensation and energetic stability exhibited by Homestead Cave's small mammals across the terminal Pleistocene environmental transition. It also suggests mechanisms for the recent breakdown of this compensation.…”
Section: Discussionmentioning
confidence: 99%
“…The energetic zero-sum dynamics hypothesis, (Ernest et al, 2008(Ernest et al, , 2009, was tested by correlation (Spearman's rank method, r s ) of geometric mean individual polychaete energy use rate with polychaete total density, D tot (hypothesis B). Similarly, the correlation between the total energy use rate and total density was also computed.…”
Section: Analyses Of Potential Mechanisms Of Changementioning
confidence: 99%
“…Note that species level compensatory dynamics may occur with or without community level compensation (Gonzalez and Loreau, 2009). Ernest et al (2008) suggested that energetic demand may be a more suitable currency than density to address the occurrence of compensatory dynamics. Further they suggest that under a metabolism-based zero-sum framework there could be a direct trade-off between population density and mean individual energy use rate (see also Ernest et al, 2009), Hypothesis B: under zero-sum dynamics, there will be a significant negative relationship between density and mean individual energy use.…”
Section: Introductionmentioning
confidence: 99%
“…Such location specific changes in the environment could have important effects on co‐occurring animal assemblages. For example, changes in precipitation levels can lead to shifts in vegetation structure and resulting changes in rodent community composition (Ernest, Brown, Thibault, White, & Goheen, 2008). The wetter marshes of Studland may have similarly affected local invertebrate and mammal assemblages, and we have shown that hierarchical modeling is better suited to uncover such effects when using EIVs.…”
Section: Discussionmentioning
confidence: 99%